Experimental behaviour of concrete-filled steel tubes under cyclic axial compression. Issue 1 (January 2020) - Cao, Vui Van; Le, Quoc Dinh; Nguyen, Phuoc Trong
This study experimentally investigated the behaviour of concrete-filled steel tubes under cyclic axial compression. A total of 42 concrete-filled steel tube specimens of two groups were tested to failure. In each group, 18 specimens were subjected to three cyclic axial loading histories while three specimens were subjected to monotonic loading for comparison. The results indicated that concrete-filled steel tube specimens under cyclic axial compression failed in the form of buckling and still kept their form which was similar to the failure of specimens under monotonic loading. Effect of cyclic axial loading slightly reduced (approximately 2%–3%) the maximum stress but it increased 25% of the strain corresponding to the maximum stress. Loading and unloading moduli in post-peak stress phase were, respectively, about 70% and 85% higher than initial moduli because better interaction and confinement were resulted from the initial loading cycle. In addition, the absorbed energy exhibited a heavy dependence on strain and confinement while it was insignificantly affected by cyclic loading histories. Details and application of obtained experimental results are reported in this article.